0438 Correlates of Subjective-Objective Sleep Discrepancy in Patients with Comorbid Fibromyalgia and Insomnia. (27th April 2018) - Chan, W S; Levsen, M P; Puyat, S; Robinson, M E; Staud, R; Berry, R B; McCrae, C S
Abstract: Introduction: Individuals with primary insomnia often have poorer subjective sleep than objective sleep, a phenomenon termed negative sleep discrepancy. Recent studies suggest that this phenomenon might differ in comorbid insomnia. This study examined sleep discrepancy, its night-to-night variability, and its demographic, clinical, and behavioral correlates in adults with comorbid insomnia and fibromyalgia. Methods: Sleep diaries and actigraphy were obtained from 223 adults with fibromyalgia and insomnia (age=51.53 [SD=11.90] years; 93% women) for 14 consecutive days. Sleep discrepancy was calculated by subtracting diary from actigraphy estimates of sleep onset latency (SOL-D), wake after sleep onset (WASO-D), and total sleep time (TST-D) for each night. Averages across 14 days were calculated for each individual. Night-to-night variability in sleep discrepancy was calculated by taking the within-individual standard deviation over 14 days. Participants also completed measures of mood, pain, fatigue, sleep/pain medications, nap duration, and caffeine consumption. Results: Average sleep discrepancies across 14 days were small (SOL-D: 7.91 mins; WASO-D: -8.32 mins; TST: 1.04 mins). However, absolute discrepancies per night were large ([SOL-D]: 44.15 mins; [WASO-D]: 32.09 mins; [TST-D]: 83.02 mins). Bland Altman plots showed that there was no consistent positive or negative discrepancy for the sleep parameters examined. The direction of sleep discrepancy varies by day and is equally likely to be either positive or negative. Night-to-night variability in sleep discrepancy was high; within-individual night-to-night variability was greater than between-individual variability. Taking prescribed pain medications, primarily opioids, was associated with greater night-to-night variability in WASO-D and TST-D. Conclusion: Unlike patients with primary insomnia, patients with comorbid fibromyalgia do not exhibit consistent negative sleep discrepancy. Absolute sleep discrepancies per night were large, but positive and negative sleep discrepancies over 14 days canceled each other, resulting fairly concordant diary and actigraphy estimates of sleep. Future research is needed to investigate the clinical significance and implications of high night-to-night variability of sleep discrepancy, and the role of prescribed opioid medications in sleep perception. Support (If Any): This research is supported by the National Institute of Arthritis and Musculoskeletal and Skin Diseases (R01AR055160; PI: McCrae).